Transpacific Engagements: Trade, Translation, and Visual Culture of Entangled Empires (1565–1898), de Florina H. Capistrano-Baker y Meha Priyadarshini - Machuca Chávez, Claudia Paulina (México y la Cuenca del Pacífico, 2024)
Reseña del libro Capistrano-Baker, F. H., Priyadarshini, M. (2020). Transpacific Engagements: Trade, Translation, and Visual Culture of Entangled Empires (1565–1898). Ayala Foundation, Inc., Getty Research Institute, Kunsthistorisches Institute in Florenz (Max-Planck-Institute).